2017
DOI: 10.3233/jad-161218
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Screening Accuracy is Robust to Premorbid IQ Variation: Evidence from the Addenbrooke’s Cognitive Examination-III and the Test of Premorbid Function

Abstract: Background: Scores on cognitive screening tools for dementia are associated with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The sample is from the same cohort as that in a previously published paper, where eligibility criteria are outlined in detail (Stott et al, 2017c). In brief, the sample consisted of two groups: (i) 102 people with mild dementia (PLWD group) and (ii) 77 people aged over 65 without dementia (OA group).…”
Section: Samplementioning
confidence: 99%
“…The sample is from the same cohort as that in a previously published paper, where eligibility criteria are outlined in detail (Stott et al, 2017c). In brief, the sample consisted of two groups: (i) 102 people with mild dementia (PLWD group) and (ii) 77 people aged over 65 without dementia (OA group).…”
Section: Samplementioning
confidence: 99%
“…Such a trend was also evident in other studies. 20,26,48 Another similar study 49 showed that in a younger age group (60-69 years) with higher educational attainment (>10 years of schooling), the majority of the population scored above 80 on the ACE-III. In contrast, a completely opposite trend was seen with the cut-off value below 80.…”
Section: Discussionmentioning
confidence: 94%
“…The sample for validation analyses is from the same cohort as that in a previously published paper, where eligibility criteria are outlined in detail . In brief, the sample consisted of two groups: (a) 102 people with mild dementia (PLWD group) and (b) 77 people aged over 65 without dementia (OA group).…”
Section: Methodsmentioning
confidence: 99%